POLA HUBUNGAN INTERAKSI ANTAR SISWA TERHADAP HASIL BELAJAR IPS KELAS IV KABUPATEN INDRAGIRI HULU - Bella Khofifah; Roan Ardhika; Zubaidah Amir; Risna Wati (Muallimuna : Jurnal Madrasah Ibtidaiyah, 2022)
The ability to interact socially is something that humans must have as social beings who always want to stay in touch with other people.The higher the social interaction of students, the higher the learning outcomes.The learning outcomes studied in this study are the fourth semester social studies learning outcomes.The goal of this study is to find out how social interaction affects how well students in grade 4 at SDN 020 Simpang IV Belilas, Indragiri Hulu Regency, learn about social studies. This research includes both correlational and quantitative research. There were 213 fourth graders in the study group. A quorum sample of sixty-four students, which is 30% of the total number of students, was used for the sampling process. Questionnaires, observation sheets, and documents for data collection. SPSS 16.0's Product Moment formula determines validity, and the Alpha formula determines reliability. Both formulas find the answer. The way that the data is being looked at is called "descrptive statistical analysis." The Pearson product-moment formula and SPSS 16.0 were used in a correlation study to test the hypothesis of a cause-and-effect relationship. As shown by the rcount value of 0.624, there was a significant link between how students interacted with each other and how well they learned,whiletheerrorrateof5%rtablefor thenumberN=64(60)was0.254.sorcount>rtable(0.624>0.254).This study found that there is a strong link between social interaction and how well students in the fourth grade at SDN 020 Simpang IV Belilas in Indragiri Hulu Regency learn about social studies. This research can be used as a reference or to help put research into action by giving teachers ideas on how to improve learning activities by giving students more responsibility in groups. Researchers who want to study how students interact with each other can also use this research as a reference or to help them do their own research. Also, more researchers are expected to take part in this researc y talking about how social interactions affect other parts of the world.